The Negotiation Dance: Time, Culture, and Behavioral Sequences in Negotiation - Adair, Wendi L.; Brett, Jeanne M. (Organization Science, 2005)
We propose a normative model of transactional negotiation in which cooperative and competitive behaviors wax and wane across four stages: relational positioning, identifying the problem, generating solutions, and reaching agreement. Based on a classic proposition of communicative flexibility in high-context cultures, we propose culture-specific dyadic movements within and across these stages. Our sample included 102 high-context dyads from Russia, Japan, Hong Kong, and Thailand; 89 low-context dyads from Germany, Israel, Sweden, and the United States; and 45 United States–Hong Kong and United States–Japan mixed-context dyads. Dyads negotiated a complex, 90-minute transaction with integrative potential. We audiotaped, transcribed, and coded their negotiations for sequences of information and influence behaviors. The unit of analysis was the action-response sequence. Results confirmed that the pattern of sequences varied across the four stages and the frequency of particular sequences varied with culture. We suggest that negotiators can use this model to manage the evolution and strategic focus of their negotiation, especially during the first two stages, when the use of influence-information sequences and reciprocal-information sequences generate the groundwork for joint gains.